Automatic screening and detection of threshold fine structure. - Heise SJ; Verhey JL; Mauermann M (International Journal of Audiology, 2008)
Audiograms measured with a high frequency resolution often show quasi-periodic ripples of up to 15dB in normal-hearing listeners. This fine structure of the threshold in quiet is commonly associated with the active processes in the cochlea. Therefore its absence is discussed in the literature as an indicator of cochlear vulnerability. In order to enable a quick detection and an objective quantification of threshold fine structure, two instruments are introduced and evaluated in this article: (1) a high-resolution tracking method for measuring fine structure ('FINESS'), and (2) an automatic fine-structure detector ('FINESS-detector'). The method is tested on 22 subjects for its reliability, its accuracy, and drifts with frequency by analysing test/retest experiments and by comparing the measured thresholds to results from a reference procedure. The results indicate that FINESS and the FINESS-detector are suitable techniques for the measurement and detection of threshold fine structure that may help to investigate further into whether fine structure is a sensitive tool for the detection of an early hearing loss.